Geography's unkept promises of education for sustainable development (ESD) on geography's wasted potential to educate for a more sustainable future - Bagoly-Simó, Péter (International research in geographical and environmental education, 2023)
For decades, geography has claimed to be the school subject with a unique and powerful contribution to Environmental Education and, subsequently, Education for Sustainable Development. Empirical evidence seems to support this agenda showcasing that geographical knowledge, defined as human-environment interaction, can better equip students with the knowledge required in relation to ESD-topics and thus help to work towards a more sustainable future than any other school subject. However, despite the efforts of the last three decades, there is a clear gap between the claim and the reality of geography's role in ESD. Therefore, using the case of Germany, this article discusses three dimensions of this gap to assist geography in making the meaningful contribution to young people's lives that it has promised for decades.